3. The Fields of Arts the General Education System the Republic of Moldova - Morari Marina (Sciendo, 2016)
The general education system identifies two approaches for encompassing arts: through the curricular field and through the extracurricular and extra-scholastic aesthetic education. The fields of arts are assigning a sector, an area of activity, a branch or a compartment. In the general education system, the fields of art have been differently formed. As a school subject, art is being studied through literature, music and fine arts. Some of them are not included in the educational plan (theatre, choreography). The statute of arts (literature, music, fine arts) in the educational system is outlined from two perspectives: art as a school subject and art as an artistic activity. The area of art shall not be reduced to a school subject or a type of arts. The artistic education in the educational system corresponds to the aesthetic education compartment and it happens in the extracurricular and extra-scholastic educational framework. According to the classic, traditional theory, the aesthetic education often is reduced to the level of artistic education. An efficient perspective in capitalizing the fields of art through education may be the extension of the artistic education borders outside the aesthetic values, by extra-aesthetic values - behavioral, moral, spiritual, social etc.